Investigating The Impact of Forensic Accounting Experience on The Ethical Commitment Of Public Accountants With The Moderating Role Of Religiosity - Aljumaili, Ali; Fakhari, Hossein (Journal of Ecohumanism, 2024)
This study aims to investigate the impact of forensic accounting experience on the ethical commitment of certified public accountants in Iraq, specifically focusing on the moderating effect of Religiosity. Data was collected from 384 Iraqi-certified public accountants published by the Society of Iraqi Certified Public Accountants in 2023. A cross-sectional survey was used to select a sample of 45 certified public accountants for the investigation. The findings demonstrate a positive correlation between the experience level in forensic accounting and various aspects of ethical commitment, such as responsibility and integrity. Furthermore, the study found that Religiosity moderated this relationship, considerably influencing these ethical factors. This study links forensic accounting experience and ethical commitment among Iraqi CPAs, broadening the forensic accounting literature. It highlights religiosity as a moderating component, showing that technical proficiency and personal values affect accounting ethics. It is novel to incorporate religiosity into the ethical paradigm of forensic accounting to explain how cultural and religious factors affect Middle Eastern professional ethics.